Gendered effects of land access and ownership on food security in rural settings in South Africa - Masuku, Mfundo Mandla; Mthembu, Zinhle; Mlambo, Victor H. (Frontiers in Sustainable Food Systems, 2023)
South Africa is one of the many countries that experience critical challenges regarding land issues, with rural women in particular having limited access to and ownership of land. This paper argues that land inaccessibility for women contributes significantly to their deprivation of economic opportunities.Secondary data on women and land ownership were extracted from main sources such as peer-reviewed articles and government gazettes. In the execution of this study, a comprehensive literature review (CLR) was conducted to illuminate the topic under investigation. The three phases (the exploration phase, the interpretative phase, and the communicative phase) of the comprehensive literature review method were adopted.The three phases (the exploration phase, the interpretative phase, and the communicative phase) of the comprehensive literature review method were adopted. The result of the review suggests that the gendered nature of land distribution contributes to the phenomenon of food insecurity that faces numerous women and their households in rural areas. The customary law is a key institutional factor that poses challenges for rural women in acquiring equal access to ownership of landland ownership compared to men. The paper recommends that the South African government had better formulate land policies that provide to women equal access to and ownership of land with men.